THE VALUES APPROACH OF CHARACTER EDUCATION TO ENHANCE EARLY CHILDHOOD EDUCATORâS COMPETENCY - Hasibuan, Rahma (Indonesian Journal of Early Childhood Education Studies, 2013)
Character education is intended to cover the whole nature of the behavior, habits, interests, abilities, talents, potential, values, and mindsets. Achieving the intention of character building there must be a strategy character education. Strategy character education is the establishment ofthe steps or procedures, methods and techniques in an effort to improve the character of early childhood educators. The strategy is based on the approach, principles, methods and techniques. This strategy is integration of character education values in the learning activities/parenting. It can be done by developing a character education values both in the substance of the material and process development activities